ANALISIS ANGKUTAN UMUM BUS DAMRI PERINTIS TRAYEK PONOROGO – TULUNG AGUNG - Febri Awalia Himawan; Rika Sylviana (Akselerasi : Jurnal Ilmiah Teknik Sipil, 2022)
AbstracThe pioneering transportation for the Ponorogo Tulungagung route, which is operated by Perum Damri Ponorogo, has become the mainstay of the community to get to Ponorogo to Tulungagung or vice versa, especially for people whose areas are passed or become the route route. The route that is passed is steep and winding because it is on the slopes of Mount Wilis. In addition to this, this route has the longest distance, which is ±60 km. This study aims to determine the performance and service quality of the Damri Perintis bus for the Ponorogo–Tulungagung route. This study uses survey methods and questionnaires. Survey to obtain data on service characteristics so that service performance can be obtained. In addition, there are questionnaires distributed to obtain public perceptions of service quality. The service characteristics are load factor 60%, service frequency is 2 times, headway is 30 minutes, average speed is 22 km/hour, travel time is 2.76 minutes/km, and the number of fleets operating is 2 buses. From these characteristics, the performance is obtained with a value of 14 or moderate. The quality of service based on people's perceptions of the Damri pioneer transportation on the Ponorogo Tulungagung route is satisfied. Keywords: Pioneer Transportation, Damri, Public Transport Performance